Advertising Progress American Business and the Rise of Consumer Marketing - Laird, Pamela Walker, 1947-; Project Muse.; Project Muse. (2019)
Contains primary source material.
The book is a documentary and pictorial examination of American advertising from the Civil War to 1920.
part 1. Production as Progress. Ch. 1. Marketing Problems and Advertising Methods as America Industrialized. Ch. 2. Owner-Manager Control of Advertising. Ch. 3. Printers, Advertisers, and Their Products. Ch. 4. Advertising Progress as a Measure of Worth -- part 2. Specialization as Progress. Ch. 5. Early Advertising Specialists. Ch. 6. Competition and Control: Business Conditions and Marketing Practices. Ch. 7. The Competition to Modernize Advertising Services -- part 3. Consumption as Progress. Ch. 8. Taking Advertisements toward Modernity. Ch. 9. Modernity and Success: Legitimating the Advertising Profession-I. Ch. 10. The Appropriation of Progress: Legitimating the Advertising Profession-II.
The text of this book is licensed under a Creative Commons Attribution-NonCommercial-No Derivatives 4.0 International License
Open access edition supported by the National Endowment for the Humanities / Andrew W. Mellon Foundation Humanities Open Book Program.
Originally published as Johns Hopkins Press in 1998
Includes bibliographical references (pages 387-451) and index.
Description based on print version record.
Keywords: Advertising -- Social aspects; Advertising; Advertising -- Social aspects -- United States -- History; Advertising -- United States -- History; United States; Electronic books; Electronic books